Economic Resilience and Gender Empowerment: A Post-Pandemic Analysis of Bangladesh's Ready-Made Garment Sector - Nelufer Nazrul; Tanni Majumder; Sarala Karki (International Journal of Social Science and Humanity, 2024)
During the recent pandemic (Covid-19), Bangladesh's Ready-Made Garments (RMG) industry, which employs mostly women, faced great challenges. This examines the resilience and resistance demonstrated by female RMG workers in Bangladesh during and after the epidemic, focusing on their efforts to seek improved working conditions and social protection. The research brings to light women's agency and activism in the industry, wherein women cooperatively undertake various actions against the oppression like protests as well as cognitions for better rights and conditions. The paper considers the role of policy-making and private firms in existing industries within workers' support, looking at the performance of the schemes geared towards safety nets and gender equality. Concentrating on different problems of the female workers of readymade garments sector, the study recommends the combined approach to deal with factors like class, ethnics and migration. In conclusion, this research affirm that female RMG workers are strong and active fighter, not the female as a passive victim and give strategies how to empower and stabilize female workers through policy analysis and industry action.